Revitalisasi Posyandu Lansia di Desa Sumbertebu Kecamatan Bangsal Kabupaten Mojokerto - Nurul Mawaddah; Yudha Laga Hadi Kusuma; Mujiadi Mujiadi; Siti Rachmah; Anndy Prastya; Arief Fardiansyah (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2019)
The implementation of posyandu for the elderly is not optimal and the lack of understanding of the elderly about the posyandu for the elderly causes a lack of participation and utilization of services by the elderly. This community service activity is carried out at the Posyandu Elderly in Sumbertebu Village with the aim to improve the skills of posyandu cadres and increase the participation of the elderly coming to the Posyandu. Revitalization activities include cadre training activities, making health promotion media, socializing the use of elderly posyandu through visits to elderly homes, assisting the implementation of elderly posyandu, and carrying out development activities in the form of elderly gymnastics (sports and group therapy (education). the results of this community service include increasing cadre skills in implementing posyandu and increasing the number of elderly visits to posyandu, optimizing the main service activities in posyandu and development activities capable of increasing the motivation of elderly people to come to the elderly posyandu.